Beyond Racial Boundaries: The Liminal Intellectuality and Authenticity of Jacobus Rudolph Razoux Kühr (1911–1918) - Muhammad Miqdad Rojab Munigar; Awaludin Nugraha; Nani Darmayanti (Universitas Negeri Padang, 2026)
This article examines the authenticity and intellectual capacity of Jacobus Rudolph Razoux Kühr (1882–1958) within the sociopolitical context of the Dutch East Indies from 1911 to 1918. It analyses his writings across four newspapers: Sin Po, Pertimbangan, De Indiër, and Perniagaan. Grounded in the premise that the colonial press functioned as a platform for ideological contestation rather than a neutral conduit, the study conceptualizes authenticity as Razoux Kühr’s reflexive awareness of his positionality as an Indo-European intellectual situated between colonial authority and Indonesian society. Furthermore, intellectuality is defined as his capacity to articulate rational critiques of colonial power relations through journalistic discourse. Methodologically, the research integrates historical methods with Van Dijk’s Critical Discourse Analysis to explore the interaction between micro-level textual strategies, social cognition, and macro-level colonial structures. The findings demonstrate that Razoux Kühr consistently advocated a liberal ideological stance that was adaptable to various editorial and sociopolitical contexts, including pluralistic engagement with Chinese nationalism, public moral critiques of colonial legitimacy, and intra-press polemics. This article contributes to Indonesian colonial historiography by illustrating how discourse analysis of the press can reveal the dynamic development of intellectual agency within the liminal social position of Indo-European actors in late-colonial society.